Cold atmospheric plasma: Its time-dependent effects on the elimination of bacterial colony on periodontal manual scalers - Veena Viswanadh; Rajesh Prabhakar Gaikwad; Rajib Kar; Vandan Nagar; Chandulal Digambarrao Dhalkari; Akshaya Banodkar; Namita Maiti (Wolters Kluwer Medknow Publications, 2023)
Background: This in vitro study investigated the time-dependent bactericidal effects of cold atmospheric argon plasma treatment of periodontal hand scalers as well as the scanning electron microscopic view of the scaler tip surfaces before and after plasma treatment. Materials and Methods: The study used 34 periodontal hand scalers which were divided into test and control groups. The scaler tips were inoculated with Escherichia coli and Staphylococcus aureus bacteria, following which the scalers in the control and test groups were subjected to conventional sterilization and argon plasma sterilization, respectively. Varying exposure times of plasma treatment were done on the test group samples to evaluate the minimum time required for complete sterilization. Subsequently, streaks were made on plate count agar using each of these instruments. The agar plates were then kept in an incubator for 24 h, following which bacterial colony count was assessed (colony-forming units/mL). Furthermore, the scanning electron microscopic (SEM) view of the scaler tip was studied before and after plasma treatment. Results: A complete elimination of bacterial load (Gram-positive as well as Gram-negative) from the instrument surface was achieved by the plasma exposure time of 15-20 s. SEM analysis did not show a significant difference before and after plasma treatment as not many organic residues were present on the scaler tip. Conclusion: Cold atmospheric pressure plasma is an efficient and time-saving method of sterilization, capable of destroying both Gram-positive and Gram-negative bacteria.